On the physiology of the lantern retractor muscle of Parechinus angulosus - Boltt, R E (Rhodes University, Faculty of Science, Department of Zoology, 1963)
From Resumé: The lantern retractor muscles of regular echinoids act in almost isometric conditions and a study of their control was considered to be of interest. The retractor muscles cannot be indirectly stimulated from the radial nerves, but proved to be very photosensitive. Their responses to light were therefore studied. The muscles show a complex pattern of contraction in response to illumination, which includes both excitatory and inhibitory components. The possible genesis of these patterns is discussed and examined in the light of the responses of the muscles to direct current stimulation and to drugs. It is concluded that many of the features of the response are undoubtedly neurogenic in origin, but that myogenic activity may possibly also be involved.
Keywords: Echinodermata -- Physiology